Performance Improvement through Skills and Work Experience at the Population and Civil Registration Office of Serang Regency - khaeruman; Tabroni (Publisher Cv. Inara, 2020)
The background of this research is that the career development of employees at the Department of Population and Civil Registration of Serang Regency tends to decline, allegedly due to a lack of skills and work experience. This study aims to determine the effect of skills and work experience partially and simultaneously on the career development of employees at the Department of Population and Civil Registration of Serang Regency. The research method used is descriptive and quantitative. The population was 84 employees at the Department of Population and Civil Registration of Serang Regency and the sample size was 84 employees, while the sampling technique used in this study was saturated sampling. The data analysis technique used includes validity test, reliability test, classical assumptions, correlation test, coefficient of determination, multiple linear regression analysis and hypothesis testing. The results of the study obtained a hypothesis test of the skill variable on career development obtained tcount> ttable (3,913> 1,989) which means significant, work experience on career development obtained tcount> ttable (4,627> 1,989) means significant, while skills and work experience on career development obtained Fcount> Ftable (51,616> 3,11) means significant.